Using infrared thermography on farm of origin to predict meat quality and physiological response in cattle (Bos Taurus) exposed to transport and marketing. (November 2020) - Cuthbertson, Holly; Tarr, Garth; Loudon, Kate; Lomax, Sabrina; White, Peter; McGreevy, Paul; Polkinghorne, Rodney; González, Luciano A.
Abstract: Temperature is used as an indicator of animals' response to external stimuli and thus it could potentially be used as an indicator or poor animal welfare and meat quality. Remote monitoring of temperature can be achieved using infrared thermography (IRT) at the farm of origin before animals are sent to slaughter. Relationships between temperatures of cattle measured using IRT on-farm and potential indicators of stress and meat quality were investigated in 481 cattle in 2 experiments, one with sea transport and another with land transport. On-farm measurements included IRT and behavioural assessment of temperament along with measurement of physiological indicators of stress and carcass traits post-mortem. Significant correlations were found between IRT and meat pH, meat colour, creatine kinase, glucose, non-esterified fatty acids, magnesium, and temperament ( P  < .05). That said, these correlations did not persist across both experiments. Current findings suggest that on-farm IRT could have the potential to assist with the detection of compromised animal welfare and predict meat quality. Highlights: Temperature can be used as an indicator of poor animal welfare. Cattle thermography and potential indicators of stress and meat quality were investigated. IRT may assist the detection of compromised animal welfare and predict meat quality.